Efeito da terapia manual no processamento da dor em pessoas com osteoartrite de joelho: uma revisão sistemática - Ribeiro, Paula Fernanda Savio (2023)
Introduction: Studies show that people with osteoarthritis of the knee (KOA) are sensitized, which occurs due to a high local nociceptive input that leads to central hyperexcitability and nociplastic changes, such as reduced effectiveness of pain inhibitory pathways. To assess perceptual responses to sensory stimuli and characterize somatosensory function or dysfunction, a set of quantitative sensory tests (QST) are used, which assess local and generalized hypersensitivity, temporal summation, and conditioned pain modulation. A manual therapy has been used as a treatment for knee osteoarthritis, in addition to being effective in reducing pain, joint capacity and physical function, it also seems to improve pain modulation, increase pain thresholds and reduce summation temporal, but we need to understand the interventions that cause this effect. Objective: This review aimed to synthesize current documents on manual therapy in people with KOA, assessed by the QST compared to placebo or other interventions. Methods: A systematic review was carried out in the CENTRAL, Embase, CINAHL, PEDro and Medline databases and the methodological quality of the studies was assessed using the PEDro scale. Results: The search found 3732 studies, of which 46 were selected for full reading and of these, only 3 met the necessary criteria for analysis. Only 3 studies were found that used manual therapy and that evaluated the pressure pain threshold. Two studies compared a manual therapy group and a placebo group, while another study divided participants into three groups, two with manual therapy and one with electrotherapy. No studies were found that used other evaluation forms, such as conditioned pain modulation or temporal summation. The studies found very different intervention methods, and only one showed a significant change in the pressure pain threshold. Conclusion: We can conclude that the findings were insufficient to show a change in pain processing after using the therapy manual in this population.